Transformation of the Post-Divorce Iddah Period in the Context of Modernization in Indonesia: An Islamic Family Law Reform in the Perspective of Maslahah Mursalah: Transformasi Masa Iddah Pasca Perceraian dalam Konteks Modernisasi di Indonesia: Sebuah Reformasi Hukum Keluarga Islam dalam Perspektif Maslahah Murlah - Nazmi, Nahdia (Transformatif, 2025)
The iddah period constitutes a pivotal phase in Islamic family law, as delineated by the Quran and hadith. In Indonesia, processes of modernization and social change have significantly transformed both the understanding and implementation of the iddah period following divorce. The Circular Letter of the Director General of Islamic Community Guidance Number P-005/DJ.III/Hk.00.7/10/2021 exemplifies governmental efforts to provide contextually relevant guidelines for contemporary challenges. This study identifies changes in the post-divorce iddah period from the perspective of maslahah mursalah, employing qualitative methods and descriptive analysis. Data were collected through interviews and literature review, with primary data sourced from purposively selected interviews with the head of the Religious Affairs Office (KUA) in Banjarbaru City. The findings indicate substantial changes in the implementation of the iddah period, shaped by social, economic, cultural, technological, and gender equality factors. The iddah period is now applied to both women and men. Reforming Islamic family law through maslahah mursalah enables greater flexibility and justice, aligning legal practice with the realities of modern society to uphold honor (ḥifẓ al-‘ird), lineage (ḥifẓ al-nasl), and social order (ḥifẓ al-niẓām al-ijtimā‘ī)